Interactive Learning of Religious Moral Values in Early Childhood Using Story-Based Audio Graphic E-Books - Chandra Asri Windarsih; Komala Komala (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research focuses on developing interactive character learning media to instill religious moral values in early childhood, specifically through story-based audio graphic E-Books. The study addresses key challenges faced by Early Childhood Education Institutions, including limited access to innovative learning media, low digital literacy among educators, and the lack of engaging approaches in teaching religious morals. Employing a mixed-method design that combines quantitative and qualitative approaches, data were collected through observations, interviews, questionnaires, and evaluation tests involving both learners and educators.The analysis utilized descriptive statistics but also inferential statistics, specifically the paired sample t-test thematic analysis to evaluate the effectiveness of the media. The findings indicate that the use of audio graphic E-Books significantly enhances children’s comprehension of religious moral values, showing up to a 90% increase in understanding compared to conventional methods. Furthermore, children demonstrated greater enthusiasm and participation in the learning process. Notably, 85% of participating educators reported improved digital literacy and greater confidence in integrating technology into their teaching practices.This study contributes to the field of early childhood education by introducing a technology-based, integrative learning model that is adaptable and applicable across various early education settings. The conclusion affirms that story-based audio graphic E-Books serve as effective, engaging, and adaptive media for teaching moral values. The research also highlights the novelty of integrating visual, auditory, and narrative components to enrich children’s learning experiences while simultaneously empowering educators to utilize digital tools more effectively.